S-95 Changes in respiratory symptoms, spirometry, and exhaled nitric oxide among home care aides performing cleaning and disinfecting using different products: a longitudinal repeated measures study - Quinn, Margaret; Sama, Susan; Sheikh, Noor; Kriebel, David; Gore, Rebecca; Lindberg, John; Galligan, Catherine; Markkanen, Pia; Karlsson, Nicole; Virji, Abbas; LeBouf, Ryan (Occupational and environmental medicine (London, England), 2021)
ObjectivesOccupational and population-based studies show that cleaning and disinfecting (C&D) tasks can increase the risk of adverse respiratory symptoms. However, quantitative evaluation of specific C&D products and practices and their impacts on respiratory health are limited. Previously, we found that 80% of home care (HC) aide visits to clients’ homes involve C&D. Increasingly, C&D ingredients are combined in single products that often contain bleach, quaternary ammonium compounds (QACs) or other respiratory irritants. So-called ‘green’ C&D products might be better alternatives but have not been evaluated for respiratory health. This study evaluated the relationship between the use of conventional and ‘green’ C&D products on respiratory outcomes.MethodsA longitudinal repeated measures study design was used. Twenty HC aides each participated in four sessions in an environmental assessment laboratory where a simulated bathroom with fixtures (toilet, tub/shower, sink) was built according to residential construction specifications. During each 40-minute session, aides performed typical C&D tasks. Three multi-purpose spray C&D products - one bleach-based (1–5% by weight sodium hypochlorite), one QACs-based (including benzyldimethyldodecylammonium chloride, benzyldimethyltetradecylammonium chloride, and benzyldimethylhexadecylammonium chloride) and one ‘green’ (plant-based thymol, active disinfecting ingredient) - and distilled water in a spray bottle were randomized among the aides’ sessions. Respiratory symptoms, spirometry, and exhaled nitric oxide (eNO, a biomarker of airway response) were measured pre-and post-session.ResultsAides reported more respiratory symptoms following use of the bleach-based product (eye, nose, throat irritation, cough, and difficulty breathing) and experienced a reduction in FEV1 (-4.3%, 95%CI: -7.4 to -1.1), compared to the other products and to distilled water. Mean eNO decreased by 10 ppb (95% CI: -8 to -13ppb) following bleach-based product use compared to the other products and to distilled water.ConclusionsBleach-based C&D products may cause acute adverse respiratory changes after a relatively short exposure representative of C&D in HC.